2017
DOI: 10.1159/000453665
|View full text |Cite
|
Sign up to set email alerts
|

C-Arm Cone Beam Computed Tomography Guidance for Radiofrequency Ablation in Hepatocellular Carcinoma

Abstract: Objective: To assess the usefulness of C-arm cone beam computed tomography (CBCT) combined with ultrasound for the treatment of hepatocellular carcinoma (HCC) by radiofrequency ablation (RFA). Methods: Patients underwent RFA following transcatheter arterial chemoembolization (TACE) or RFA alone under ultrasound or CBCT guidance combined with ultrasound-based techniques. They were divided into 2 groups based on the use (C group) and nonuse (NC group) of CBCT guidance. The technical success of RFA and local tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…And with the technique, TACE and MWA can be performed on the same working bed sequentially during one intervention. Following TACE, we now use DynaCT to scan the tumor and reconstruct 3D images for the puncture site and the route planning [28]. Wang needle can accurately penetrate the target lesions of 46 patients and achieve favorable clinical results [29].…”
Section: Discussionmentioning
confidence: 99%
“…And with the technique, TACE and MWA can be performed on the same working bed sequentially during one intervention. Following TACE, we now use DynaCT to scan the tumor and reconstruct 3D images for the puncture site and the route planning [28]. Wang needle can accurately penetrate the target lesions of 46 patients and achieve favorable clinical results [29].…”
Section: Discussionmentioning
confidence: 99%
“…During RFA, the puncture process can be monitored in real time under fluoroscopy and needle deployment can be accurately adjusted according to the location of the lesion, which more effectively creates a sufficient ablation zone as a safety margin. 13,20 In order to further understand role of CBCT in image-guided RFA, this current study retrospectively reviewed and compared the clinical data from patients that had undergone CBCT-guided RFA with those that had undergone conventional s-CT-guided procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, RFA guided by CBCT has received increasing attention and application, showing unique technical advantages compared with s-CT guidance, but few published studies have reported on the difference between the two image-guiding modalities, especially in liver cancer. 1315…”
Section: Introductionmentioning
confidence: 99%
“…Other new techniques include magnetic resonance, C‐arm CT positron emission tomography‐CT (PET‐CT), CT‐fiber bronchoscope, and electromagnetic navigation bronchoscopy (ENB) …”
Section: Imaging Guidancementioning
confidence: 99%